Implementation of a rehabilitation nursing homecare program in patients with chronic obstructive pulmonary disease - Casado, Sónia (2016)
To evaluate the effects of a respiratory rehabilitation nurse program at home of clients with COPD requiring supplemental oxygen. Methods: We identified 15 clients diagnosed with COPD, requiring home oxygen therapy. During 15 sessions of home RR were taught/trained breathing exercises, therapy management, energy conservation techniques and strengthening exercises. Were performed evaluations of the oxygen peripheral saturation (SpO2), peak expiratory flow (PEF), Medical Research Council Dyspnoea Scale Questionnaire (mMRC), London Chest Activity of Daily Living (LCADL) and Euro Qol. Development: We conducted a baseline assessment to 15 users (70,20±12,03 years), 12 men and 3 women. COPD is diagnosed for an average of 15,27±10,24 years and the oxygen treatment is performed for and average of 7,27±3,99 years. We have found a statistically significant increase in SpO2 final assessment (97,4±1,12%) when compared to baseline (92,2±1,78%), as in the PEF (290,67±141,5L/min and 164,0±69,78L/min, respectively). On the scale mMRC we observed a statistically significant decrease in the sensation of dyspnoea (baseline assessment of 3±0,76 and post-intervention assessment of 2,4±0,91). In assessing the LCADL, there was a statistically significant improvement between baseline and post-intervention (34,33±9,07 and 26,47±7,99 respectively). At Euro Qol VAS users reported an improvement in his health over the course of the RR comparing the two evaluations periods (40,67±5,94 at baseline and 58±6,76 in post-intervention). Conclusions: The patients evaluated had statistically significant improvements in SpO2 values, in PEF and in the results of the scales used, when comparing the two evaluations moments. These data confirm that the RR is translated into health gains for users with COPD.